2010
DOI: 10.1007/s12274-010-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective synthesis of hexagonal Ag nanoplates in a solution-phase chemical reduction process

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…The hexagonal symmetry of the scattered spots in the SAED pattern (Fig. 2c-d) also suggests the existence of a single crystalline triangle and hexagonal shape nanoplates bounded by (111) planes [22,23]. The TEM images agree with the UV-visible SPR for the generation of the SNPs.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…The hexagonal symmetry of the scattered spots in the SAED pattern (Fig. 2c-d) also suggests the existence of a single crystalline triangle and hexagonal shape nanoplates bounded by (111) planes [22,23]. The TEM images agree with the UV-visible SPR for the generation of the SNPs.…”
Section: Resultssupporting
confidence: 61%
“…During the progress of the reaction, the UV-vis spectra show the appearance of two new peaks near 370 and 470-495 nm. The observed peaks are contrary to a single SPR band in the range of 390-450 nm for spherical silver nanoparticles [13,14] and attributed to reduction in symmetry with the formation of hexagonal or triangular SNPs [1,22]. The TEM images showed that the light brown SNPs solution contains a non-aggregated triangle, truncated triangle and hexagonal shape nanoplates (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, the reaction exposing to the blue LED appeared in green colour with the presence of two SPR peaks at 412 and 595 nm, suggesting the formation of non-spherical AgNPs [31]. Although the right-shifted SPR peak may indicate the formation of larger sizes of AgNPs [30], the newly emerged SPR peak in the range of 495-630 nm aside from the original SPR peak at 416-418 nm is the characteristics of non-spherical AgNPs [32]. The control reactions with no light exposure and no DNA remained in yellow colour with the SPR peaks at 420 and 413 nm, respectively, indicating the presence of spherical Figure 1.…”
Section: Syntheses Of Different-shaped Agnpsmentioning
confidence: 92%